Inhibitors of Mitochondrial Dynamics Mediated by Dynamin-Related Protein 1 in Pulmonary Arterial Hypertension - Xiao, Fan; Zhang, Rui; Wang, Lan (Frontiers in Cell and Developmental Biology, 2022)
Pulmonary arterial hypertension (PAH) is a chronic, lethal pulmonary disease characterized by pulmonary vascular remodeling. It leads to malignant results, such as rupture of pulmonary arterial dissection, dyspnea, right heart failure, and even death. Previous studies have confirmed that one of the main pathological changes of this disease is abnormal mitochondrial dynamics, which include mitochondrial fission, fusion, and autophagy that keep a dynamic balance under certain physiological state. Dynamin-related protein 1 (Drp1), the key molecule in mitochondrial fission, mediates mitochondrial fission while also affecting mitochondrial fusion and autophagy through numerous pathways. There are various abnormalities of Drp1 in PAH pathophysiology, including Drp1 overexpression and activation as well as an upregulation of its outer mitochondrial membrane ligands. These aberrant alterations will eventually induce the development of PAH. With the process of recent studies, the structure and function of Drp1 have been gradually revealed. Meanwhile, inhibitors targeting this pathway have also been discovered. This review aims to shed more light on the mechanism of Drp1 and its inhibitors in the abnormal mitochondrial dynamics of PAH. Furthermore, it seeks to provide more novel insights to clinical therapy.